Degree-Based Topological Properties of Molecular Polymeric Networks Composed by Sierpinski Networks. (8th October 2021) - Rauf, Abdul; Ishtiaq, Muhammad; Faraz Qaiser, Hafiz; Aslam, Adnan; Anoh Yannick, Kraidi
Abstract : Sierpinski graphs are a widely observed family of fractal-type graphs relevant to topology, Hanoi Tower mathematics, computer engineering, and around. Chemical implementations of graph theory establish significant properties, such as chemical activity, physicochemical properties, thermodynamic properties, and pharmacological activities of a molecular graph. Specific graph descriptors alluded to as topological indices are helpful to predict these properties. These graph descriptors have played a key role in quantitative structure-property/structure-activity relationships (QSPR/QSAR) research. The objective of this article is to compute Randic index (R − 1 / 2 ), Zagreb index M 1, sum-connectivity index SCI, geometric-arithmetic index GA, and atom-bond connectivity ABC index based on ev-degree and ve-degree for the Sierpinski networks S n, m .